How to Apply for a Greenbelt Agricultural Tax Assessment - Raychel Thomas; Jana Caracciolo; Catherine G. Campbell (EDIS, 2021)
This publication is for current or potential farm operators who are interested in knowing more about how the Florida Greenbelt Law affects farm operations’ property taxes and how farm operations can apply to receive an agricultural tax assessment. Written by Raychel Thomas, Jana Caracciolo, and Catherine Campbell, and published by the UF/IFAS Department of Family, Youth and Community Sciences, July 2021.